Murdoch mysteries. Season 04 [videorecording (DVD)] - Coons, Cal; Bisson, Yannick, 1969-; Joy, Hélène; Craig, Tom, 1962-; Jennings, Maureen (Acorn Media, 2012)
In the late 19th century, Toronto city police Detective William Murdoch takes a new, more scientific approach to murder investigation.